2010
DOI: 10.1002/cmdc.201000157
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Eimeria tenella CDK‐Related Kinase 2: From Target Identification to Lead Compounds

Abstract: Apicomplexan parasites encompass several human-pathogenic as well as animal-pathogenic protozoans like Plasmodium falciparum, Toxoplasma gondii, and Eimeria tenella. E. tenella is the causative agent of coccidiosis a disease of chickens, which causes tremendous economic losses to the world poultry industry. Considerable increase of drug resistance makes it necessary to develop and pursue new therapeutic strategies. Cyclin-dependent kinases (CDKs) are key molecules in the regulation of the cell cycle and are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…There are a high number of anti-cancer drugs that interfere with cell cycle regulation, leading to the death of the rapidly dividing cells (Tamamori et al , 1998; Doerig et al , 2002; Monaco & Vallano, 2003; Malumbres & Barbacid, 2009). Therefore, we, like others, predict that the disruption of the parasite’s cell cycle will lead to its death (Engels et al , 2010; Waters & Geyer, 2003). …”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…There are a high number of anti-cancer drugs that interfere with cell cycle regulation, leading to the death of the rapidly dividing cells (Tamamori et al , 1998; Doerig et al , 2002; Monaco & Vallano, 2003; Malumbres & Barbacid, 2009). Therefore, we, like others, predict that the disruption of the parasite’s cell cycle will lead to its death (Engels et al , 2010; Waters & Geyer, 2003). …”
Section: Introductionmentioning
confidence: 65%
“…We were able to clone one of the identified E. tenella cyclins (EtCYCs) (EtCYC3a) and demonstrated that its protein product was able to activate EtCRK2, in a similar manner to that shown with the non-cyclin activator Xenopus laevis rapid inducer of G2/M progression in oocytes (XlRINGO) (Engels et al , 2010; Ferby et al , 1999). In a combined in vitro and in silico high-throughput screening approach, using real (3514 compounds) and virtual (approx.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Engels et al validated EtCRK2 as a drug target using the cyclin-dependent kinase-specific inhibitor flavopiridol, (IC 50 of 33 nM and Ki of 11 nM) which was similar to the human isoform (IC 50 36 nM, Ki 19 nM). They also identified four chemically diverse compounds with Ki values in the low micromolar range [68]. …”
Section: Generic Substratesmentioning
confidence: 99%